Cattle and Railroads – The Flint Hills Connection - Phil Miller (Symphony in the Flint Hills, 2010)
For centuries the lush grasses of the Kansas Flint Hills were the domain of the American Bison. But the coming of railroads in the 1860s signaled a change in the life of the prairie … the end of the Bison’s reign and the arrival of domesticated cattle. By 1867 the Kansas Pacific Railway had reached Abilene, and the cattle drives from Texas along the Chisholm Trail brought cattle to Abilene for shipment to the packinghouses of Kansas City, St. Joseph and points east.
Keywords: American Bison; buffalo; railroad; Kansas Pacific Railway; Chisholm Trail; Texas; Abilene; Kansas City; St. Joseph; Missouri; cattle; cows; cowboy; ranch; drive; farm; tradition; old; cattlemen; Flint Hills; Chase County; land; McFarland; Hymer; Cassoday; Council Grove; Bazaar; Clements; Elmdale; Eskridge; Aikman; Cedar Point; Beaumont; Matfield Green; tracks; steam engine; train; Santa Fe; DDT; dip tank; corral; packinghouse; childhood